The message of Joel, Micah, and Habakkuk : listening to the voice of God - Prior, David, 1940-; Prior David (Downers Grove, Ill. : InterVarsity Press, 1999)
Where is God in times of disaster? How can God allow suffering? What are God's people to do about moral decay in society? While people throughout the ages have long pondered these questions, three of the minor prophets--Joel, Micah and Habakkuk--provide insights to these perennial problems. The people of Joel's day were devastated by a locust plague, which Joel said warned of the coming Day of the Lord. Micah rebuked a culture of corruption and moral evil. Habakkuk cried out to the Lord on account of a society bent on violence. All three point to a transcendent God who gives hope in times of uncertainty. David Prior's passage-by-passage exposition of these three books provides careful study and measured insight and application for today's church.
The message of Joel -- Cry to God (1:1-20) -- Return to God (2:1-17) -- Rejoice in God (2:18-32) -- Fear God (3:1-21) -- The message of Micah -- Preface (1:1) -- Micah's message to the world (1:2-16) -- The preacher for this people (2:1-13) -- Micah's message to the leadership of the nation (3:1-12) -- Micah's message of a future beyond the ruin of Jerusalem (4:1-5:15) -- A message of gloom and doom (6:1-7:7) -- A message of light and love (7:8-20) -- The message of Habakkuk -- Dialogue with God (1:1-17) -- A double vision (2:1-20) -- Habakkuk's prayer (3:1-19).
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc